Role of urine glycosaminoglycan levels in the diagnosis and follow-up in men with lower urinary tract symptoms. - ŞEKERCİ, ÇAĞRI AKIN (My University, 2024)
Objective: The aim of this study was to investigate whether urinary glycosaminoglycans (GAG) levels reflect clinical status in men with lower urinary tract symptoms and if they could be used as a marker in management of overactive bladder (OAB). Methods: A total of 34 patients were recruited who were admitted with LUTS and diagnosed as having clinically bladder outlet obstruction (BOO) due to prostate enlargement. These newly diagnosed, never treated patients underwent routine investigation, consisting of history, physical examination, PSA, ultrasound, uroflowmetry, assessment of symptoms scored by both International Prostate Symptom Score (IPSS) and Marmara- Overactive Bladder Questionnaire (M-OBQ). The patients were divided into two groups as those with an initial M-OBQ score < 12 (group 1) and ≥ 13 (group 2). Alfa blocker was initiated in eligible patients. Further evaluations included prostate volume measurement, pre- and post-treatment urinary GAG levels, IPSS and M-QAOB values and maximum urine flow rate (Qmax). Results: Before treatment, urinary GAG level was 21.5 mg/gCr (6.1-45.5) in Group 1, and 23.35 mg/gCr (15.6-32.6) in Group 2 (p =0.845). After the treatment, the GAG level in Group 1 and Group 2 were found to be 19.8 mg/gCr (7.4-70.5) and 18 (7.6- 41.7), respectively (p = 0.511). No difference in GAG levels was found in subgroup analysis for patients with or without OAB. Conclusions: In recent years, there have been many studies investigating the relationship between LUTS and urinary markers. However, in our prospective study, no relationship was found between pre- and post- treatment urinary GAG levels in patients with LUTS with or without OAB. Key wORDS: GAG; Bladder outlet obstruction; Overactive bladder; Biomarker.
Keywords: GAG; Bladder outlet obstruction; Overactive bladder; Biomarker.